The Effectiveness of Using Context Clues Strategies in Teaching Vocabularyof Descriptive Text - Lenni Oktaviana Rangi; Suhartono, Luwandi; Sumarni, Sumarni (Edu-Ling: Journal of English Education and Linguistics, 2024)
To language, vocabulary is like a well-stocked toolbox to a carpenter. The more tools possessed, the better the product will be. Likewise, vocabulary is the core of all English skills both spoken and written. Concerning its importance, this research aimed to discover whether or not context clues strategy is influential for students’ learning of vocabulary in descriptive text as well as its effect size score. This quantitative research was carried out by the use of a Pre-Experimental design with a single group. The sample of this research was the tenth graders of SMKN 1 Belitang Hilir. The data were gathered by using the technique of pretest and posttest in the form of objective questions. The data were then analyzed statistically using the employed procedures, namely the calculation of variants, deviations, correlation, hypothesis testing, and derived formulas in gaining the effect size. The findings showed that the pretest and posttest respectively resulted in the mean score of 53,51 and 69,19 with the effect size of 1,64. Herewith, the use of context clues strategy has a strong and significant effect in enhancing students’ vocabulary of descriptive text.